[Different drums ; Dapithapon ; Dancing attorneys [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Military story focusing on the latest peace initiative offered by the government to rebel soldiers led by ex-Lt. Col. Gregorio Honasan. A story about how people who are growing old cope with living alone. Attorneys teaching ballroom dancing and providing a dancing escort service for a fee.
Different drums (17 min.) -- Dapithapon (15 min.) -- Dancing attorneys (13 min.)
VHS
Keywords: Young Officers Union; Armed Forces of the Philippines -- Corrupt practices; Aged -- Philippines -- Interviews; Aged -- Philippines; Recreation